The Potential Risk of Hearing Loss on Noise-Exposed Housewives : An Observational Study at Sukosari Madiun Railway Residentia - Kartika Elisabet Krisnanti; Lilis Sulistyorini (Universitas Airlangga, 2020)
Introduction: Hearing loss events often occur in communities who exposed to high-intensity noise and for long periods. Residents who lived around the railway tracks had a high risk of experiencing hearing loss. This study aims to analyze the potential risk of hearing loss in housewives who for 1x24 hours was always exposed to train noise. Method: This research was an observational analytic study with a cross-sectional design. The sample of this study was 42 housewives who were divided into 2 groups: 21 people exposed to noise and 21 people not exposed to noise. Respondents were selected using a simple random sampling technique. Research data obtained through interviews and observations. Measurement of noise intensity using a whisper test. Result and Discussion: Measurement of day and night noise (L = 65,9 dBA) has exceeded the noise quality standard set for residential areas which were 55 dBA. The results showed that noise (p = 0,030; OR = 5,846) had a strong correlation with hearing loss. While age (p = 0,416), length of stay (p = 1,000), the presence of a barrier (p = 0,465) did not have a significant correlation with hearing loss. Conclusion: Housewives who were exposed to noise have the potential risk of hearing loss. Therefore, efforts must be made to adjust the distance of the settlement and the installation of sound dampers to reduce the risk of hearing loss.